Eliciting carbohydrate-specific immune response against sialosides: success and challenges. (April 2011) - Ling, Chang-Chun; Bundle, David R
Chemoenzymatic synthesis has been shown to be a powerful adjunct to carbohydrate chemistry since it allows chemists to prepare a wide range of complex carbohydrate analogs in large amounts and with unparalleled efficiency. Here we summarize investigations conducted in our group into the synthesis and immunochemistry of tumor-associated gangliosides and the development of a chemoenzymatic route to αα(2→→8)-linked oligosialosides by probing substrate binding to the enzyme, αα(2→→8)-sialyltransferase.